Laboratory investigation of crest height statistics in intermediate water depths - Karmpadakis,I; Swan,C; Christou,M (Proceedings of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2019)
This paper concerns the statistical distribution of the crest heights associated with surface waves in intermediate water depths. The results of a new laboratory study are presented in which data generated in different experimental facilities are used to establish departures from commonly applied statistical distributions. Specifically, the effects of varying sea-state steepness, effective water depth and directional spread are investigated. Following an extensive validation of the experimental data, including direct comparisons to available field data, it is shown that the nonlinear amplification of crest heights above second-order theory observed in steep deep water sea states is equally appropriate to intermediate water depths. These nonlinear amplifications increase with the sea-state steepness and reduce with the directional spread. While the latter effect is undoubtedly important, the present data confirm that significant amplifications above second order (5–10%) are observed for realistic directional spreads. This is consistent with available field data. With further increases in the sea-state steepness, the dissipative effects of wave breaking act to reduce these nonlinear amplifications. While the competing mechanisms of nonlinear amplification and wave breaking are relevant to a full range of water depths, the relative importance of wave breaking increases as the effective water depth reduces.